Nitrogen Rate and Initiation Date Effects on Stockpiled Tall Fescue During Fall Grazing in Tennessee - Nave, Renata L. G.; Barbero, Rondineli P. [UNESP]; Boyer, Chris N.; Corbin, Michael D.; Bates, Gary E. (Alliance Crop Soil & Environmental Science Soc-acsess, 2016)
In Tennessee, N is one of the most common limiting nutrients for tall fescue [Schedonorus arundinaceus (Schreb.) Dumort] production. Rising prices for N fertilizer have pressured cow-calf producers in Tennessee to reevaluate N management alternatives. The objectives of this study were to determine the effect of initiation date and N fertilization on stockpiled tall fescue yield, nutritive value, animal performance during fall grazing, and overall profitability of the production system. The research was conducted in tall fescue pastures at the Plateau AgResearch and Education Center in Crossville, TN from August 2013 to December 2014. A completely randomized design with three replications was applied to existing tall fescue pastures. Stockpile initiation dates were 1 August and 1 September, and N fertilization rates were 0 and 60 lb/acre N. With the exception of crude protein (CP) and in vitro dry matter digestibility (IVDMD), all other plant-related variables analyzed in this study showed a significant difference among monthly grazing periods. Nitrogen fertilization rate did not affect forage mass or nutritive value in both years. There were no significant interactions between initiation date and N fertilization rate for all animal performance measures. Data from this study suggests that with low beef prices ($0.75/lb), profits are maximized by initiating stockpiling in August with no N application.